2018
DOI: 10.1108/bij-10-2017-0281
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of critical failure factors (CFFs) of Lean Six Sigma in real life scenario

Abstract: Purpose Many projects focus on the reliable operation of the activities in the project. Any failure in the process activities leads to major problems resulting in waste, defects, equipment damage, which has a direct impact on the consumers. In addition, Lean Six Sigma (LSS) is not new to this issue. LSS projects have faced an interruption in the process flow and unforeseen defects. Therefore, the purpose of this paper is to identify the vital failure factors of LSS projects. Design/methodology/approach Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 62 publications
0
75
0
1
Order By: Relevance
“…The target population for the study was members of a green movement in India, with potential knowledge and awareness on green consumerism. The questionnaire was distributed via email using total Dillman's approach (Sreedharan, Gopikumar, Nair, Chakraborty, & Antony, 2018). Through convenient sampling, the respondents posing the intention for green purchases and basic knowledge on green practice were chosen as respondents for the study.…”
Section: Model Evaluationmentioning
confidence: 99%
“…The target population for the study was members of a green movement in India, with potential knowledge and awareness on green consumerism. The questionnaire was distributed via email using total Dillman's approach (Sreedharan, Gopikumar, Nair, Chakraborty, & Antony, 2018). Through convenient sampling, the respondents posing the intention for green purchases and basic knowledge on green practice were chosen as respondents for the study.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Belhadi et al (2019) identified them for small and medium enterprises (SME). Sreedharan et al (2018) established them for manufacturing and service enterprises. Jha et al (2019) established CSF for LSS in Indian manufacturing companies.…”
Section: Critical Success Factors (Csf) For Lean Six Sigma (Lss) Using Quality 40mentioning
confidence: 99%
“…Sindhwani et al (2019) reported CSF when LSS is implemented with other strategies, e.g., Agile and Green. CSF for LSS use in a nonspecific business unit are also available (Laosirihongthong et al 2006;Sreedharan et al 2018). Yadav et al (2021) established 18 critical success factors for Lean Six Sigma under Quality 4.0 framework.…”
Section: Critical Success Factors (Csf) For Lean Six Sigma (Lss) Using Quality 40mentioning
confidence: 99%
See 2 more Smart Citations